Brönsted Acidic Ionic Liquid 1-(1-Propylsulfonic)-3-methylimidazolium-Chloride Catalyzed Hydrolysisof D-Cellobiose in Aqueous Medium. (10th April 2012) - Amarasekara, Ananda S.; Wiredu, Bernard
Abstract : Brönsted acidic ionic liquid 1-(1-propylsulfonic)-3-methylimidazolium chloride (PSMIMCl) shows a higher catalytic activity than sulfuric acid in the hydrolysis of D-cellobiose to D-glucose in water at 90–120 ° C. This catalytic activity enhancement is more significant at higher temperatures, and at 120 ° C, PSMIMCl produced 64.5% glucose yield, whereas H2 SO4 produced only 42.2% after 40 min. reaction, and this is a 52.8% enhancement of catalytic activity due to the alkylimidazolium group attached to the sulfonic acid group. 1 H NMR monitoring of the D-cellobiose hydrolysis in PSMIMCl and sulfuric acid mediums failed to reveal intermediates in the hydrolysis reaction, and this is probably due to rapid conversion of the intermediate(s) to a mixture of D-glucose anomers with α : β ≈ 1 : 1.6 .